2021
DOI: 10.1002/2211-5463.13318
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between pathogens and Atg8 family proteins: thousand‐faced interactions

Abstract: Autophagy is an intracellular degradation and recycling process that can also remove pathogenic intracellular bacteria and viruses from within cells (referred to as xenophagy) and activate the adaptive immune responses. But autophagy—especially Atg proteins including Atg8 family members—can also have proviral and probacterial effects. In this review, we summarize known interactions of bacterial, parasitic, and viral proteins with Atg8 family proteins and the outcome of these interactions on pathogen replicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
(97 reference statements)
0
6
0
Order By: Relevance
“…Besides vIRF-1, other viral proteins that can interact with ATG8 proteins have been reported [ 8 , 38 ]. For example, the matrix protein M2 of influenza A virus has been verified experimentally to contain a conserved LIR motif, which is required for binding to and redistributing LC3 to the plasma membrane, thereby subverting antiviral autophagy (virophagy) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides vIRF-1, other viral proteins that can interact with ATG8 proteins have been reported [ 8 , 38 ]. For example, the matrix protein M2 of influenza A virus has been verified experimentally to contain a conserved LIR motif, which is required for binding to and redistributing LC3 to the plasma membrane, thereby subverting antiviral autophagy (virophagy) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plant autophagy research is focused on the function in the cytoplasm where selective autophagy works [ 11 ]. However, recent studies have shown that ATG8 interacts with various proteins in the nucleus [ 74 , 75 ]. Pathogen proteins might affect autophagy activity through ATG8 interaction in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…The collection of a few dozen experimentally characterized LIR motifs made it possible to develop computational methods for their prediction [ 19 , 20 ]. Such prediction tools have inevitably facilitated the advancement of research toward identifying the molecular mechanisms underlying several subtypes of selective macroautophagy and related biological processes [ 21 ], and the number of scientific publications reporting the experimental validation of functional LIR motifs continues to accumulate. Despite the importance of experimentally verified LIR motifs, for wet lab biologists and computational biologists alike, there is a lack of a central repository of LIR-motif instances curated from the literature describing such sequences across species.…”
Section: Introductionmentioning
confidence: 99%